Effectiveness Test Of Hot Water Treatment On Mango (Mangifera Indica) Affected By Fruit Fly Stings With Different Temperature And Time Variations - Mohammad Lukmanul Hakim; Wiharyanti Nur Lailiyah; Suhaili .Suhaili; Adiet Cantyo Pamungkas (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: This study was conducted to highlight the effectiveness of Hot Water Treatment (HWT) as an alternative environmentally friendly method of controlling fruit flies (Bactrocera spp.) on mango (Mangifera indica) fruit, and to determine the optimal combination of temperature and soaking time without damaging the fruit quality. Method: The study used 36 mangoes soaked in hot water at temperatures of 45°C, 50°C, 55°C, and 60°C for 30, 60, and 90 seconds. Evaluation was carried out on the number of larvae that emerged after 7 days post-treatment, as well as observations of the visual condition of the skin and flesh of the fruit. Results: Treatment with a temperature of ≥55°C for 60–90 seconds showed a significant decrease in the number of larvae, from an average of 4.67 larvae (control) to 1 larva. These results also showed no significant visual damage to the fruit at a temperature of 55°C. Conclusion: The combination of temperature of 55°C for 60 seconds is the most optimal treatment, because it is able to kill fruit fly eggs and larvae without causing damage to the skin or flesh of the fruit. Novelty: This study shows that the HWT method can be applied practically and effectively as an alternative post-harvest control at the farmer level, without leaving chemical residues. Conclusion: HWT at a temperature of 55°C for 60 seconds is an optimal and sustainable method for controlling fruit flies without reducing the quality of mango fruit. Article Type: Experimental Research.